Development of a Korean Medicine Online Program on Mental Health - Hye In Jeong; Kyeong Han Kim (Korean Pharmacopuncture Institute, 2023)
Objectives: The coronavirus disease 2019 has deteriorated mental health, particularly in mothers with elementary school children. Although the country has developed several health promotion programs to preserve mental health, no program has incorporated Korean medicine. Thus, this study focuses on developing vital Korean medicine mental health care programs.Methods : : The program follows the Korean medicine health promotion program principles. Guidelines, reports, research, and previous programs were analyzed to form interventions and lecture content.Results : : Pellets, hot packs, meditation, lavender oil, and green tea were selected as final intervention strategies. Mental health-related guidelines were analyzed to produce stress management lecture materials. In addition, an operational methods and evaluation tool manual was created.Conclusion : : We designed a health promotion program capitalizing on Korean medicine to improve mental health. This program will be assessed and accordingly improved through practical applications.